Legal Implications of Marriage During the 'Iddah Period: Analytical Study of the Opinions of Fiqh Scholars - Bariah, Oyoh; Ferianto, Ferianto (International Journal Ihya' 'Ulum al-Din, 2024)
Divorce between a man and a woman, whether due to death, divorce, or a court decision, results in the application of the law of 'iddah (a waiting period) in Islam.  Compilation of Indonesian Islamic Law (KHI) Chapter VI Article 40 letter b concerning the Prohibition of Marriage, that it is prohibited to enter into a marriage if a woman is still in the 'iddah period with another man. This marriage prohibition applies to both men and women simultaneously.'Iddah is a stipulation of Allah's Shari'a for women who have broken up with their marital relationship to carry out the waiting not to get married at a certain time to hifdz an-nail that guarantees the honor of the child's lineage in the family so that by 'iddah the woman's womb is clean from pregnancy and the most basic goal of ‘iddah is for ta'abbudi. So, based on ta’abbbudi, the law of carrying out 'iddah is obligatory and sinful for those who break it, both men and women. So, The legal implications for those who marry during the 'iddah period, either iddah due to death or divorce for both men and women who have or have not had sexual intercourse, are that marriage is broken (faced) and must be annulled, and if they have had sexual relation, both of them' you have committed adultery and sinned, even according to Imam Malik because of sexual intercourse, it is haram for a husband who marries a woman during 'iddah to remarry that woman forever. Jumhur ulama allows both men, whether the first husband who divorced her or the second husband who marries a woman during the 'iddah period, to remarry her on condition that the woman has carried out her two periods of 'iddah perfectly, furthermore allowed to marry the man she chose.